CASH FLOW, DEBT ISSUANCE, EQUITY ISSUANCE, AND FIXED ASSET INVESTMENT ON MANUFACTURE COMPANY 2010-2014CASH FLOW, DEBT ISSUANCE, EQUITY ISSUANCE, AND FIXED ASSET INVESTMENT ON MANUFACTURE COMPANY 2010-2014 - Palupi, Ritma (Universitas Dr. Soetomo, 2020)
Matters about financing decision based on pecking order theory’s hierarchy are currently appealing. This research strives to discover how corporate’s fixed asset investment reacts to cash flow, debt issuance, and equity issuance. Researcher uses 75 samples of manufacturing company in Indonesia during 2010-2014 period with 199 firm-year observation. Multiple linear regression’s result indicates that cash flow and debt issuance have influence towards corporate’s fixed asset investment, but the equity issuance have no influence towards corporate’s fixed asset investment. Also regression coefficient exhibits that manufacturing company in Indonesia follows pecking order theory’s hierarchy. Cash flow’s influence towards fixed asset investment is more significant than debt issuance’s, and debt issuance’s influence is stronger than equity issuance. This points out that corporate’s fixed asset investment is more sensitive towards cash flow (internal fund) compared to debt issuance (external fund), and so is debt issuance is more sensitive compared to equity issuance. With all that in mind, it is concluded that manufacturing company in Indonesia follows pecking order theory in terms of financing decision, which uses internal fund at first then started to use external fund if deemed necessary.